STRATEGIC MANAGEMENT IN THE GOODS DISTRIBUTION SYSTEM: THEORETICAL OVERVIEW AND CATEGORY’S CLARIFICATION - BILUKHA, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The dynamic and turbulent market environment imposes specific requirements on the ability of business entities to promptly identify, analyze, and respond to challenges in the field of goods distribution. This, in turn, necessitates the implementation of effective strategic management to ensure the resilience, competitiveness, and long-term development of enterprises. Despite the importance of strategic management in distribution, the lack of clear conceptual foundations and unified approaches to defining its essence complicates the integration of various aspects into a cohesive system. From this perspective, the article examines the approaches of domestic and foreign authors to defining strategic management. The author emphasizes that this economic category represents a multidimensional process that integrates the formation of long-term goals and the strategic vision of an organization, focusing on the need to consider external environmental factors and adapt to dynamic changes. The primary objective of this process is to ensure competitive advantages and sustainable organizational development. At the same time, scientific and practical approaches often lack a clearly defined structure for strategic management, which creates challenges for its effective implementation in management practices. Based on a content analysis of existing definitions presented in scientific sources and using a structural-logical approach, the essence of strategic management in distribution has been refined. Strategic management of distribution is proposed to be understood as a set of managerial actions aimed at ensuring the availability of goods and services for target consumers, considering their needs and demands, by selecting optimal distribution channels, establishing beneficial interaction among their participants, and organizing efficient logistics and sales of finished products. Thus, the proposed approach combines the key aspects of strategic management definitions found in the literature and conceptually reflects the essence and content of distribution.
Keywords: strategic management; distribution; marketing activity; logistics activity; commercial activity; distribution channels; goods movement; sales